Primary care providers and hypertension in pregnancy: Reflections on a patient encounter - Jagidesa Moodley; Prakash Jugnanden; Mergan Naidoo; Nnabuike C. Ngene (South African Family Practice)
In South Africa, large numbers of individuals with medical emergencies initially visit a general practitioner or family physician. In the case of maternity care, this may occasionally involve acute onset of severe hypertension during the antenatal period. Primary care providers (PCPs) are therefore faced with the conundrum of treating and stabilising high blood pressure or referring the patient to an appropriate hospital. Case reviews within groups of medical practitioners provide an opportunity for learning in the practical management of obstetric emergencies. The case history of a patient with severe hypertension was presented, and reflections on this patient encounter were highlighted. Amongst the challenges faced by generalists in their interactions with the public health sector are availability of standard clinical protocols, medicines, the need to work in partnership and the need to have ‘feedback’.